Regulasi Kecemasan Dengan Dzikir Dalam Sudut Pandang Psikologi Tasawuf - Qonitah Tsabitah Azmi; Shifa Salsabilah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Various methods have been used to treat anxiety disorders, ranging from medication, cognitive medication, cognitive, and spiritual methods. One of the most effective approach in overcoming anxiety to be researched is the practice of dhikr in the Sufism tradition as a method of anxiety regulation.dhikr in the Sufism tradition as a method of anxiety regulation. This research aims to expand the understanding of Sufism and the practice of dhikr, and to support the development of effective spiritual-based interventions that are effective in overcoming anxiety. To achieve the research objectives, this study used the literature review method with a content analysis technique. The results showed that dhikr is one of the recommended psychospiritual methods to overcome or minimize anxiety. minimize anxiety. This is because, by dhikr and remembering Allah SWT. Peace and mental balance will be easier to achieve.